Relação entre a qualidade da água e a transformação do uso do solo da bacia hidrográfica do Tibagi. - Ferreira, José Hilário Delconte (2009)
This study was developed in a project of research and development (R&D) approved by ANEEL and financed by COPEL Geração SA. The study was developed in Tibagi river basin (TRB) in the base years of 1987, 1991, 1997, 2001 and 2007. The north hypothesis of the work was: different uses of land result in different qualities of water. Thus, the main goal of this study was to characterize the transformation of the land use during the period. Characterize the water quality index (WQI) during the entire studied period and compare the transformation of the land use with the WQI variation. The characterization of the land use was carried out based on Landsat orbital images, using ENVI, ARCGIS and SPRING softwares. WQI was calculated using WNA and SUDERHSA data to eleven stations, being seven stations in Tibagi river and 4 stations in tributaries of Tibagi river. It was suggested a land occupation quality index (LOQI), generated from data of land use, pedologic and slope, that varies from 10 to 100 (being LOQI value of 100 - the best possible quality) to correlate the land use with WQI in TRB. The work was divided in four chapters, being the first one labelled "Differentiation of forestry of eucalyptus and pinus in the region of Tibagi river basin". In this chapter, it was verified the efficiency of the vegetation suppression tool of ENVI, applied to the year of 2007, of ENVI in the identification of forestry. In the second chapter, "The evolution of the land in Tibagi river basin based on a multi-temporal analysis by remote sensing", it was reported about the transformation of the land use during the period (1987-2007) to the entire basin comparing its occupation with the forestry code. The third chapter, titled "Water quality index (WQI) in Tibagi river basin (TRB) - state of Paraná", stated about the characterization of WQI in the basin to all the years of study. In the fourth chapter, "Correlation between water quality and land use applied to Tibagi river basin - PR", it was correlated the land use with the WQI and indicated a land occupation quality index (LOQI) that presented high correlation with WQI.